2012
DOI: 10.1371/journal.pone.0036264
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq Identifies SNP Markers for Growth Traits in Rainbow Trout

Abstract: Fast growth is an important and highly desired trait, which affects the profitability of food animal production, with feed costs accounting for the largest proportion of production costs. Traditional phenotype-based selection is typically used to select for growth traits; however, genetic improvement is slow over generations. Single nucleotide polymorphisms (SNPs) explain 90% of the genetic differences between individuals; therefore, they are most suitable for genetic evaluation and strategies that employ mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
138
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 59 publications
3
138
0
Order By: Relevance
“…Comparisons of GH-transgenic and domestic salmonids with slower growing wildtype controls suggest the somatrophic axis may influence growth via a variety of genes, including those related to carbohydrate, lipid, and energy metabolism, cell/tissue structure, development, and the response to stress (Rise et al 2006;Devlin et al 2009Devlin et al , 2013Tymchuk et al 2009;White et al 2013;Xu et al 2013). Similarly, RNAseq analysis and additional microarray studies using rainbow trout muscle have identified genes related to lipid and carbohydrate metabolism, ATP production (Salem et al 2012;Kocmarek et al 2014), muscle components (Salem et al 2012), and transcription factors (Kocmarek et al 2014) to be differentially expressed between large and small fish. Although these studies have been effective at identifying which genes are differentially expressed in fish with different growth phenotypes they are less able to link expression of the gene to particular QTL.…”
Section: Introductionmentioning
confidence: 99%
“…Comparisons of GH-transgenic and domestic salmonids with slower growing wildtype controls suggest the somatrophic axis may influence growth via a variety of genes, including those related to carbohydrate, lipid, and energy metabolism, cell/tissue structure, development, and the response to stress (Rise et al 2006;Devlin et al 2009Devlin et al , 2013Tymchuk et al 2009;White et al 2013;Xu et al 2013). Similarly, RNAseq analysis and additional microarray studies using rainbow trout muscle have identified genes related to lipid and carbohydrate metabolism, ATP production (Salem et al 2012;Kocmarek et al 2014), muscle components (Salem et al 2012), and transcription factors (Kocmarek et al 2014) to be differentially expressed between large and small fish. Although these studies have been effective at identifying which genes are differentially expressed in fish with different growth phenotypes they are less able to link expression of the gene to particular QTL.…”
Section: Introductionmentioning
confidence: 99%
“…If coverage is deep enough, biases are addressed and appropriate experimental replicates are included; differences in gene expression can also be detected between samples [70]. Transcriptome sequencing is usually performed at the individual level, but it is also possible to estimate allele frequencies from sequencing of pooled samples [71] and to compare different lines and populations [72]. Variant identification from transcriptome data can suffer the same biases from low coverage sequences as Poolseq experiments and can also suffer from allelic dropout when only certain alleles are expressed in individual samples.…”
Section: Methods For Generating Genomic Datamentioning
confidence: 99%
“…Presently RNA-Seq is being widely used in functional genomics studies both in aquaculture and their related model species like Zebrafish (Hegedus et al, 2009;Aanes et al, 2011;Ordas et al, 2011) catfish , Atlantic cod (Johansen et al, 2011), rainbow trout (Lewis et al, 2010;Salem et al, 2010), European eel (Coppe et al, 2010) and spotted gar (Amores et al, 2011). Salem et al, (2012) using RNA sequencing identified about 22 SNP markers and 1 mtDNA haplotype with growth traits in rainbow trout. studies whole genome transcriptome in rainbow trout exposed to various stress conditions using RNA sequencing.…”
Section: Transcriptome Sequencingmentioning
confidence: 99%